Calculation of thermodynamic properties and transport parameters of C6F12O - Li, Dajian; Rao, Xiajin; Zhang, Xiaoxing; Peng, Boya; Pan, Shaoming; Huang, Wei; Ma, Shouxiao (Frontiers in Materials, 2022)
With the increasing demand for environmental protection, the research on environmentally friendly gas insulating media in the power industry has received increasing attention. C6F12O has good insulating properties and has the potential to be used as an insulating medium in gas-insulated equipment. Previous researches show that thermodynamic properties and transport parameters can reflect the microscopic properties of plasma and evaluate the physical properties of gas during gas discharge. In this paper, the thermodynamic and transport properties of C6F12O are calculated based on LTE conditions. According to the type of particles participating in the reaction and the thermal parameters of themselves, the number density of particles at different temperatures can be obtained. Then, the thermodynamic properties and transport parameters in the range of 300K~30000K are calculated by combining the partition function and collision parameters. The results show that the conductivity of C6F12O is higher than that of CO2 and N2 at lower temperatures, which is consistent with the properties of most electronegative gases. The thermal conductivity of C6F12O has distinct peaks at 3500K, 5500K and 16000K, respectively. The calculation results can provide a data basis for the subsequent calculation of breakdown and interruption characteristics, which is significant to the design and development of gas insulating equipment.